2013
DOI: 10.1073/pnas.1310643110
|View full text |Cite|
|
Sign up to set email alerts
|

Reversible DNA methylation regulates seasonal photoperiodic time measurement

Abstract: Significance This work examined whether epigenetic mechanisms participate in the regulation of seasonal reproduction. In long-day (summer) breeding hamsters, exposure to inhibitory winter photoperiods, or winter-like patterns of melatonin, altered DNA methyltransferase expression; decreased DNA methylation in the proximal promoter region of deiodinase type III ( dio3 ) in the hypothalamus; and, in turn, increased hypothalamic dio3 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
162
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(166 citation statements)
references
References 48 publications
3
162
1
Order By: Relevance
“…During muscle cell differentiation, dio2 gene expression is up-regulated by histone demethylation and acetylation leading to myoblast differentiation (32), whereas dio3 sits in an imprinted locus, tightly regulated by epigenetic mechanisms essential for normal growth and viability (33). In addition, it has been reported that photoperiodic information regulates dio3 gene expression by acting upon promoter methylation in adult Siberian hamsters (34). In view of these results, we favor a hypothesis where TSHR-mediated changes in the epigenetic regulation of dio2 gene expression underlie the shift in TSH sensitivity caused by the MPP effect on fetal TSH signaling.…”
Section: Discussionmentioning
confidence: 99%
“…During muscle cell differentiation, dio2 gene expression is up-regulated by histone demethylation and acetylation leading to myoblast differentiation (32), whereas dio3 sits in an imprinted locus, tightly regulated by epigenetic mechanisms essential for normal growth and viability (33). In addition, it has been reported that photoperiodic information regulates dio3 gene expression by acting upon promoter methylation in adult Siberian hamsters (34). In view of these results, we favor a hypothesis where TSHR-mediated changes in the epigenetic regulation of dio2 gene expression underlie the shift in TSH sensitivity caused by the MPP effect on fetal TSH signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In diverse reproductive events, hormone-driven temporal changes of DNA methylation have been revealed. For example, to control seasonal reproductive neuroendocrine function in the hamster, thyroid hormone reversibly reduces promoter DNA methylation and upregulates expression of photoperiodic sensor gene dio3 (51). During transition from follicle to corpus luteum after ovulation, LH induced DNA methylation and histone modifications are associated with repression of the inhibin α expression in the ovary (52).…”
Section: Dna Methylation and Uterine Physiologymentioning
confidence: 99%
“…For example, it has been shown that the timing of flowering in plants (induced by seasonal changes in day length) involves various epigenetic modifications, including DNA methylation (Yaish et al 2011). Moreover, in mammals, DNA methylation of the type III deiodinase (dio3) gene has recently been shown to be critical for measuring photoperiod (Stevenson and Prendergast 2013).…”
mentioning
confidence: 99%